A QoE-Based Framework for Video Streaming Over LTE-Unlicensed - Mohamed S. Hassan; Mahmoud H. Ismail; Taha Landolsi; Ibtihal Ahmed; Fatema M. Aseeri (IEEE Access)
To improve the system capacity and accommodate the ever-increasing demand for bandwidth by the network users, LTE service providers have turned their attention to the unlicensed industrial, scientific, and medical (ISM) spectrum; currently heavily utilized by the users of the IEEE 803.11 standards or WiFi. Unfortunately, such an approach, referred to as LTE-U, causes co-existence problems which necessitates the development of effective spectrum-sharing mechanisms to mitigate the interference with WiFi users. In this work, we propose a framework for video transmission over LTE-U to achieve harmonious coexistence with WiFi systems while taking into account the quality of experience (QoE) requirements of the user equipment (UE). In the proposed scheme, the channel allocation aims to enhance the peak signal-to-noise ratio (PSNR) and to reduce the end-to-end delay of video packets. We present analytical schemes for predicting PSNR and delay of the received video sequence based on video parameters transmitted by the video server and periodic feedback from the UE, which provides the signal-to-noise ratio (SNR) of the channel. In addition, the probability of causing interference to WiFi users is used to formulate the channel allocation problem as a multi-objective optimization problem. Taking into account the received video quality and the achieved inter-frame delay for both LTE-U and WiFi users, the simulation results show that the proposed scheme outperforms a reference model that employs a channel access mechanism but randomly assigns frames to the available channels.